As concepções de Professoras e de Auxiliares sobre a atuação docente promotora de práticas educativas de boa qualidade com bebês - Silva, Kátia Cristina Fernandes e (2019)
The present study analyzed the conceptions of teachers and assistants who work in daycare about the teaching performance that promotes good quality educational practices with babies in institutions with different pedagogical proposals. Its theoretical basis was constituted essentially by the contributions of the current Historical Partner of Human Development of Vigotski (2007) and Wallon (2007) and researchers from the field of Pedagogy of Childhood (OLIVEIRA-FORMOSINHO, 2001; OLIVEIRA-FORMOSINHO, KISHIMOTO and PINAZZA, 2007; FORTUNATI, 2009; BARBOSA, 2009 and 2010; FREIRE, 2014). The research had as main assumptions the understanding that teaching with babies denotes singularities involving aspects such as knowledge (TARDIF, 2002; TARDIF and LESSARD, 2011; CAMPOS and ROSEMBERG, 1995; MACHADO 1998; GARCIA et al, 2018) and beliefs (OLIVEIRA-FORMOSINHO, 2011) and that contexts influence educational practices (OLIVEIRA-FORMOSINHO, 2002; TOBIN et al, 2008). The data were constructed based on the qualitative approach, more specifically, inspired by ethnographic studies (ANDRÉ, 1995; BOGDAN and BIKLEN, 2006; LAKATOS and MARCONI, 2003), in two groups of babies, in two nurseries located in Fortaleza, with Proposals. Distinct pedagogicals. For this, the following procedures were used: participant observation, individual and collective semi-structured interviews with the teachers and assistants, responsible for the classes, document consultation and questionnaire application. The records were made in field diary, photographs and audio recorder. The data analysis indicates that: 1) “good quality educational practices” are linked to “objective conditions of the context that are essential for them to happen”, such as materials and spaces; “characteristics that cannot be lacking in the relationship with children”, such as affection, dialogue, care, attention and respect (public daycare); and to “pedagogical intentionality”, how to teach content that children have to learn (private nursery); 2) “baby teacher” corresponds to the image of someone who needs to “have” specific attributes, such as knowledge about affectivity / emotion, responsibility and patience (public daycare); take care and “give” attention; “Show and call” the teacher to record the possible advances of the child (private daycare) and “do” certain “tasks”, such as understanding the child, solving conflicts, differentiating children's crying (public daycare), facing challenges, making discoveries and teach children to wait (private nursery); 3) the pedagogical proposals underway in the institutions contribute to the professionals to point out different knowledge needed by the teacher so that she can perform good quality educational practices, among them: the importance of interactions between babies and older children; the adequacy of planning to the needs and interests of children (public daycare); and the organization of children through “speech / monologue / music” to fulfill the adult's commands (private nursery); 4) the main source of knowledge for the development of good quality educational practices with babies is not the Pedagogy course; knowledge derives, above all, from the way each subject experienced a particular practice, notably in other formative contexts other than the university, or through attempts at errors and successes.